Blue Skies, Blue Seas : Air Pollution, Marine Plastics, and Coastal Erosion in the Middle East and North Africa - Heger, Martin Philipp; Vashold, Lukas; Palacios, Anabella; Alahmadi, Mala; Bromhead, Marjory-Anne; Acerbi, Marcelo (Washington, DC: World Bank, 2022)
This book shows how virtually all forms of natural capital, but particularly “blue” natural capital – skies and seas – has been degrading in the Middle East and North Africa (MENA) region over the last three decades, and focuses on the three challenges of air pollution, marine plastics, and coastal erosion. MENA’s cities are on average more than 5 times as air-polluted as recommended by the WHO guidelines, and not a single MENA city, which reported data, meets them. MENA’s seas are amongst the most plastics-polluted in international comparison, particularly so the Mediterranean. Coastal erosion relentlessly eats away at the coastline, particularly so in the Maghreb region, where coastal erosion is about 10 times faster than the global average, which is 7 mm per year. This natural capital degradation has effects on people and the economy, which are assessed in this book. In terms of health impacts, ambient air pollution causes about 270,000 premature mortalities each year and is responsible for about 60 days of disease over the lifetime of the average MENA resident. In addition, the book reviews the evidence on the detrimental effects of microplastics, not only for the ecosystem, but also for human health. In terms of livelihood impacts, the effects or marine plastics and coastal erosion are reviewed and the costs to the blue economy, especially the tourism and the fisheries sectors, are assessed. The economic damages from the three priority areas, air pollution, marine plastics, and coastal erosion are estimated to amount to about 3 percent of regional GDP every year. Policy recommendations for getting to clean blue skies and blue seas are prepared. The recommendations elaborate on (a) how monitoring the degradation and providing information about its sources can be improved, (b) how market-based incentives for more sustainable blue resource use can be designed, (c) the kinds of regulatory reforms needed to strengthen institutions, and (d) the types of investments needed to move towards blue skies and blue seas.